Recovery Plan for Scots Pine Blister Rust Caused by Cronartium pini - Kim, Mee-Sook; Hantula, Jarkko; Kaitera, Juha; Zambino, Paul J; Woodward, Stephen; Richardson, Bryce A; Stewart, Jane E; Spaine, Pauline; Shaw, Dvaid C; Takeuchi, Yu; Klopfenstein, Ned (Scientific Societies, 2022)
Scots pine blister rust caused by Cronartium pini, which includes the fungal rust pathogen with either a heteroecious life cycle (previously known as Cronartium flaccidum) or an autoecious life cycle (formerly known as Peridermium pini or Endocronartium pini), is capable of infecting many Eurasian pines including Pinus sylvestris (Scots pine). The heteroecious form of C. pini completes its life cycle alternating between pines and various species of flowering plants (Angiospermae); the related autoecious form spreads directly from pine to pine. If the Scots pine blister rust pathogen possesses or gains the capacity to infect North American pines, the economic and ecological impacts could be significant. Scots pine is one of the most widely distributed conifers in the world, and it has become naturalized in the northeastern and midwestern United States. Scots pine blister rust is also called resin-top disease and top-dieback of pine. Symptoms in pine include stem swelling, branch flagging, excessive pitch flow, and top-kill, and, in the alternate hosts, leaf spotting. The rust pathogen is spread in nature by wind-borne spores, which require live hosts for infection. However, the rust pathogen can also be transported on infected plant materials that can be nonsymptomatic. Early infections of host plant infections by C. pini are difficult to detect and diagnose, but molecular techniques offer a potential approach for early detection and diagnosis. This recovery plan is intended to provide a brief summary of the disease, assess the status of critical recovery components, and identify disease management research, extension, and education needs.
Keywords: fungi; invasive species; forest damage; Pinus sylvestris; Metsämänty; Scots pine blister rust; Tervasroso; Peridermium pini; Cronartium flaccidum; Cronartium pini